Use of the Tei Index in the Conservative Management of TRAP Sequence Pregnancies Diagnosed during the Periviable Period: A Case Series - Kristina Martimucci; Theresa Kuhn; Robyn Bilinski; Jesus Alvarez-Perez (Case Reports in Obstetrics and Gynecology)
Twin Reverse Arterial Perfusion (TRAP) Sequence is a rare complication of monochorionic pregnancies. Without intervention, the viable pump twin in a case of TRAP Sequence may develop high output cardiac failure leading to an intrauterine fetal demise. We present 3 cases of TRAP Sequence pregnancy diagnosed during the second or third trimesters of pregnancy. There are minimal sonographic tools for the guidance of a fetal therapeutic interventional procedure during the second trimester or timing of delivery during the third trimester to reduce morbidity and mortality of a viable fetus. Tei index may be a useful sonographic tool in the management of TRAP Sequence during the second or third trimester of pregnancy.